Physico-chemical Studies of Soil Samples of Tribal Area Surrounding Dahod, Gujarat, India - Patel, B.S.; Dabhi, H.R. (Asian Journal of Chemistry, 2010)
Dahod is a district place, situated at the boarder of three states Gujarat, Madhya Pradesh and Rajasthan, India. The soil samples from 10 different villages of tribal area surrounding Dahod were collected. The physicochemical properties such as moisture content, specific gravity, pH measurement and estimations of Mg2+, Na+, K+ and Cl–, HCO3–, PO43-, NO3-% of carbon were studied.